3D auxetic metamaterials with tunable multistable mechanical properties - Zhang, Bojian (2025)
Multistable mechanical metamaterials have been extensively studied for their unique mechanical behaviors, including snap-through capability, variable stiffness, and recoverable cushioning properties. Similarly, auxetic metamaterials, known for their ability to uniformly distribute stress, absorb energy efficiently, and withstand complex loading conditions, offer significant potential for the development of safer, more durable, and efficient materials. Despite significant progress in the field, a key challenge remains unaddressed: the effective integration of both multistability and auxetic properties in 3-dimensional (3D) mechanical metamaterials. This integration has not been fully explored, particularly regarding the realization of programmable, directionally tunable behaviors that combine the advantages of a negative Poisson's ratio and multiple stable states. Here, we introduce a 3D mechanical metamaterial composed of isotropic bistable auxetic blocks (BABs) fabricated using bi-material 3D printing technology. Mechanical models are developed to assess the influence of geometrical parameters on the mechanical responses of BAB, which are validated through both numerical simulation and experimental results. By assembling these proposed BABs, we demonstrate that 3D mechanical metamaterials with multistable auxetic behavior can be designed and fabricated. Our results show that these metamaterials exhibit sequential deformation under applied loading and possess programmable mechanical properties. These findings open new avenues for the design and development of 3D multistable auxetic metamaterials with programmable mechanical behaviors, offering promising applications in areas such as energy absorption, deployable structures, soft robotics, and more.